Environment variables on IT adoption: a case of Nigerian construction organizations - Waziri, Abdullahi Y. (Penerbit UTM Press, 2015)
Pirm’s external environment combines many attributes and plays a vital role in IT adoption. Technological innovations are adopted as organizational reactions to change and for influencing the business environment. This study examined the effect of external environment on IT adoption in construction organizations. Specifically, the study empirically explores the external variables, assessed their effects and determined how they can optimally be combined to enable IT acceptance. The data collected was analysed using structural equation modelling analytical approach. Results of the analysis revealed that external environment strongly influence firm’s IT adoption with a path coefficient of 0.70 and a z-value of 10.5. Furthermore, a confirmatory factor analysis conducted confirmed competitive pressure, government support and market uncertainty as the most significant variables of firm’s external environment in relation to IT implementation with a standardized parameter estimates of 0.75, 0.51 and -0.41 respectively. Precisely, competitive pressure and government support were strongly and positively related to IT adoption while market uncertainty exhibited a strong but negative relationship. It was recommended that managers of construction organizations should, strategically, overcome the pressures they exert from their competitors for improved market share and general organizational performance. Furthermore, government should strive to provide adequate IT infrastructures and enablers within its responsibilities such as adequate electricity, incentives and clear IT policy.